Public health policies for children and youth with special health care needs in OECD member countries and Brazil: A scoping review protocol. - Ângela Cristina Rocha Gimenes; Elenir Rose Jardim Cury (PLoS ONE)
Background Because public health policies lay down guidelines for health promotion in specific populations, a review of policies devised for children and youth with special health care needs (CYSHCN) can reveal the actual degree of priority assigned to this population segment, while also highlighting relevant policies in this field. Objective To map the available evidence of public health policies for CYSHCN in member countries of the Organization for Economic Cooperation and Development (OECD) and Brazil. Method A scoping review protocol was developed as per the Joanna Briggs Institute (JBI) manual and the Preferred Reporting Items for Systematic Review and Meta-Analyses-Extension for Scoping Reviews (PRISMA-ScR) checklist, for application to the Web of Science (WoS), Scopus, PubMed, and Embase databases;to theLatin American and Caribbean Literature in Health Sciences (LILACS)multilingual thesaurus; and to gray literature.The review will map the principal documents (irrespective of time frame or language) addressing public health policies for CYSHCN up to 19 years old. The research protocol has been registered on the Open Science Framework platform (identifier 10.17605/OSF.IO/UW5BH:DOI). Results and conclusion Tables, maps, charts, and/or graphs accompanied by descriptive texts will be employed to present the results to the research question and provide answers to it. Use of both open-access software IRaMuTeQ for similitude analysis and word clouds is also planned. This protocol is expected to reveal policies that meet the specific needs of this vulnerable population segment and highlight examples of good practices or current gaps.